HUBUNGAN ANTARA FINANSIAL STRESS DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DIKOTA PALOPO - Sandi, Andi Tenri; Husmaruddin, Husmaruddin; Firmanzah, Adi (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Financial stress or financial stress is a psychological condition that arises from the inability of individuals to meet financial needs adequately and efficiently. The purpose of this study is to examine the relationship between financial stress and lifestyle on student financial management in the city of Palopo. This study uses a quantitative method with data collected through a questionnaire.the sample used is relatively limited, namely 100 respondents. Using the slovin formula and random sampling. Data analysis was carried out with SPSS 27. The results of the study showed that the financial variable stress had a significant positive influence on financial management, while lifestyle did not have a significant influence on financial management. The insignificance of the influence of lifestyle on financial management shows that students in Palopo City are relatively able to adjust consumption patterns with limited resources. This research contributes to the development of science in the field of financial psychology and behavioral economics, especially related to the relationship between financial stress and lifestyle to student financial management, especially in the city of Palopo.